The Social and Psychological Impact of Traumatic Events and Torture in a Bosnian Civilian Population - Arcel, Libby Tata (Array, 2003)
Trauma is in this article documented not only as a psycho-physiological process but also as social suffering. Applying the psychological/psychiatric approach and the social impact approach on the torture survivor clients in CTV we found an extremely high level of experienced traumatic events and torture and an equally high level of experienced social suffering as a consequence of these experiences. Survivors that have experienced high intensity and high frequency of torture show clearly higher levels of psychological symptoms than people that have experienced low frequency and intensity. The question of a reciprocal relation between symptoms due to torture and socioeconomic difficulties is discussed. The socioeconomic problems aggravate the consequences of torture and the torture itself aggravates the socioeconomic difficulties. Health and Mental Health scientists should be explicit about the social and economic consequences of trauma thus mobilising political consciousness and social action in the field of social rehabilitation.